2015
DOI: 10.1093/heapro/dav049
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk and sexual health among female migrants in China

Abstract: SummarySexual behavior is the dominant mode of HIV transmission in China, and young female migrants are among the populations at highest risk. This article examines how HIV-related risk behaviors among female migrants might vary according to workplace settings. Participants were young female migrants recruited from three workplace settings-factories, restaurants and entertainment venues. In a crosssectional survey, we assessed 457 participants' sociodemographic characteristics, HIV/AIDS-related knowledge, cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 26 publications
1
23
1
Order By: Relevance
“…The current study brings attention to the behavioral risk for HIV and other STIs/GTIs and low rates of HIV testing among female migrants working in entertainment venues in China. Although employment in entertainment venues can bring financial benefits to young women, especially in comparison with other potential forms of employment such as factory or restaurant work (Huang et al, 2013), this analysis reveals substantial health challenges among these young female migrants. In addition to sexual risk factors, we observed other health problems such as high prevalence of problem drinking (57%) and mental health problems including recent depression symptoms (19%) and suicidal ideation (9%).…”
Section: Discussionmentioning
confidence: 96%
“…The current study brings attention to the behavioral risk for HIV and other STIs/GTIs and low rates of HIV testing among female migrants working in entertainment venues in China. Although employment in entertainment venues can bring financial benefits to young women, especially in comparison with other potential forms of employment such as factory or restaurant work (Huang et al, 2013), this analysis reveals substantial health challenges among these young female migrants. In addition to sexual risk factors, we observed other health problems such as high prevalence of problem drinking (57%) and mental health problems including recent depression symptoms (19%) and suicidal ideation (9%).…”
Section: Discussionmentioning
confidence: 96%
“…The majority of migrated people in Vietnam are young adults with middle-level education status and they migrate to more urban areas mainly for employment reasons [1]. Previous studies indicated that moving to a new workplace may expose these migrant workers to new social networks, ideas, behaviors, or even socially isolated situations that could alter their lifestyle choices, including engaging in sexual risk behaviors [2]. Migrant workers are often subjected to harassment, exploitation, and violence, which may lead to poor health outcomes, and they may also face barriers to health care in the host country, such as limited or lack of health insurance and entitlement to statutory health care [3].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the growing body of scholarship examining intersectionalities in relation to literacies, the vast majority of literature that considers female sexualities within the context of literacy frameworks does so within health sciences, such as how literacy access influences sexual behaviors relative to sexually transmitted infections (e.g., Blodt, Holmberg, Muller-Nordhorn, & Riekmann, 2012; Champion, Harlin, & Collins, 2013; Huang et al, 2016; Park et al, 2017). Examinations of secondary literacies emphasizing female sexuality are rare and nearly always focus on Black girls.…”
Section: Literature Reviewmentioning
confidence: 99%